Microstructure and Mechanical Properties of Nb–Ti–V–Zr Refractory Medium-Entropy Alloys - Jia, Yuefei; Zhang, Liangbo; Li, Peiyou; Ma, Xindi; Xu, Long; Wu, Shiwei; Jia, Yandong; Wang, Gang (Frontiers in Materials, 2020)
Low-density refractory medium entropy alloys (NbTiVZr, Nb0.5TiVZr, and NbTiV) were produced by vacuum arc melting, then heat-treated at 1,200°C for 1 h, water quenched, and finally annealed at 500°C for 0.5 h. Their respective microstructures, elevated-temperature (600–1,000°C) mechanical properties, and thermal expansion behavior were then investigated. All the alloys are characterized by a BCC structure with a grain size of c. 85–135 μm. The results demonstrated that NbTiVZr alloy exhibits relatively high yield strength and specific strength at 600, 800, and 1,000°C. Moreover, a low coefficient of thermal expansion was also obtained for this alloy when the temperature was below 750°C. This study provides guidance for the engineering application of low-density refractory medium entropy alloys at elevated temperatures.